Endometrial cancer and oral contraceptives: an individual participant meta-analysis of 27 276 women with endometrial cancer from 36 epidemiological studies - Collaborative Group On Epidemiological Studies On Endometrial Cancer (Elsevier, 2015)
Background Oral contraceptives are known to reduce the incidence rate of endometrial cancer, but it is uncertain how long this effect lasts after use ceases, or whether it is modified by other factors. Methods Individual participant datasets were sought from principal investigators and provided centrally for 27 276 women with endometrial cancer (cases) and 115 743 without endometrial cancer (controls) from 36 epidemiological studies. The relative risks (RRs) of endometrial cancer associated with oral contraceptive use were estimated using logistic regression, stratified by study, age, parity, body-mass index, smoking, and use of menopausal hormone therapy. Findings The median age of cases was 63 years (IQR 57–68) and the median year of cancer diagnosis was 2001 (IQR 1994–2005). 9459 (35%) of 27 276 cases and 45 625 (39%) of 115 743 controls had ever used oral contraceptives, for median durations of 3·0 years (IQR 1–7) and 4·4 years (IQR 2–9), respectively. The longer that women had used oral contraceptives, the greater the reduction in risk of endometrial cancer; every 5 years of use was associated with a risk ratio of 0·76 (95% CI 0·73–0·78; p<0·0001). This reduction in risk persisted for more than 30 years after oral contraceptive use had ceased, with no apparent decrease between the RRs for use during the 1960s, 1970s, and 1980s, despite higher oestrogen doses in pills used in the early years. However, the reduction in risk associated with ever having used oral contraceptives differed by tumour type, being stronger for carcinomas (RR 0·69, 95% CI 0·66–0·71) than sarcomas (0·83, 0·67–1·04; case-case comparison: p=0·02). In high-income countries, 10 years use of oral contraceptives was estimated to reduce the absolute risk of endometrial cancer arising before age 75 years from 2·3 to 1·3 per 100 women. Interpretation Use of oral contraceptives confers long-term protection against endometrial cancer. These results suggest that, in developed countries, about 400 000 cases of endometrial cancer before the age of 75 years have been prevented over the past 50 years (1965–2014) by oral contraceptives, including 200 000 in the past decade (2005–14).